Future Seeds: Protecting food for the world - International Center for Tropical Agriculture (Bioversity International and the International Center for Tropical Agriculture, 2021)
Future Seeds is a state-of-the-art genebank under construction in Palmira, Colombia, at the Americas Hub for the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT). It is a global innovation hub for the conservation and use of crop diversity set to become a driving force for innovation in agriculture. Future Seeds will not only hold in trust for humanity the largest collections of beans, cassava and tropical forages in the world, with over 67,000 distinct samples, but will also expand its collections to other essential crops and their wild crop relatives, thus supporting global food and nutrition security. A new home for thousands of crop collections, Future Seeds aims to safeguard the world's crop diversity to ensure a climate-resilient and food-secure future for generations to come.